Implementation of Journalistic Language in the Organization Category of Visi Nusantara Online Media - Wahyunengsih, Wahyunengsih; Awaliyah, Syifa (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The use of journalistic language cannot be separated from the journey of print media in everyday life. The meaning conveyed through arranged words can give birth to meaning. Understanding related to the implementation of journalistic language must be in accordance with the rules or guidelines of journalistic language, so that a journalist is required to master the rules of writing journalistic language. The purpose of this study is to determine the application and characteristics of journalistic language characteristics used by the news category of the Visi Nusantara online media organization, then to find out the impact of the news category for students who are active in organizations. The researcher conducted a document analysis on Visi Nusantara’s organizational category news as many as 18 news editions in 2022. The results show that the characteristics of journalistic language consist of simple, short, dense, straightforward, clear, clear, interesting, populist, logical, democratic, grammatical, avoiding speech, foreign words and terms, appropriate diction, prioritizing active sentences, avoiding technical words or terms, and submitting to ethical rules. The existence of this category of news has a positive impact on students because the news contained is packaged informatively, although there are some mistakes in the writing, it does not rule out the possibility of this news becoming a field of information and inspiration for students and people who play a role in the world of organizations. Keywords: journalistic, journalistic language, organization, Visi Nusantara